Analysis of Wireless Network Performance at Universitas Teknologi Digital Indonesia using Quality of Service (QoS) Method - Aprian Pradipta Eka Sihono; Rikie Kartadie (Teknik Informatika Universitas Pamulang, 2026)
This study aims to analyze the quality of wireless network services in the Universitas Teknologi Digital Indonesia (UTDI) laboratories based on Quality of Service (QoS) parameters, namely throughput, packet loss, delay, and jitter, using the TIPHON standard as a reference. The main issue addressed is the lack of measurable evaluation of laboratory network performance despite the increasing demand for connectivity to support academic activities. Network measurements were conducted over five working days during active lecture hours when network usage was relatively high. The collected data were processed in CSV format and analyzed to calculate the daily average of each QoS parameter and classify them according to TIPHON quality categories. The results indicate an average throughput of approximately 2.4 Mbps, packet loss of about 1.2%, delay values below 65 ms, and jitter around 4 ms. Based on the TIPHON standard, these results place the wireless network service quality in the UTDI laboratories within the “Good” to “Excellent” categories. These findings suggest that the laboratory wireless network is sufficiently reliable to support internet-based learning activities and online academic services. Furthermore, the study demonstrates that a structured QoS analysis workflow implemented using Google Colab provides a systematic and replicable approach for evaluating wireless network performance in educational environments.